2010
DOI: 10.1177/1947601910395578
|View full text |Cite
|
Sign up to set email alerts
|

The ETS Gene ETV4 Is Required for Anchorage-Independent Growth and a Cell Proliferation Gene Expression Program in PC3 Prostate Cells

Abstract: Chromosomal abnormalities that give rise to elevated expression levels of the ETS genes ETV1, ETV4, ETV5, or ERG are prevalent in prostate cancer, but the function of these transcription factors in carcinogenesis is not clear. Previous work in cell lines implicates ERG, ETV1, and ETV5 as regulators of invasive growth but not transformation. Here we show that the PC3 prostate cancer cell line provides a model system to study the over-expression of ETV4. Migration assays, anchorage independent growth assays, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 36 publications
7
73
0
Order By: Relevance
“…2). Both of these factors have been implicated in the physiology of cancer and development: polyomavirus enhancer activator 3 (PEA3) plays critical roles in invasion, migration, and proliferation of cancer cells, [28][29][30] and epithelium-specific ETS transcription factor-1 (ESE-1) mRNA is upregulated at least 6-fold after mouse EC cells differentiate. 31) Together with the previously published findings, our expression data suggest that the ETS factors PEA3 and ESE-1 play important roles in pluripotent and tumorigenic EC cells.…”
Section: Resultsmentioning
confidence: 99%
“…2). Both of these factors have been implicated in the physiology of cancer and development: polyomavirus enhancer activator 3 (PEA3) plays critical roles in invasion, migration, and proliferation of cancer cells, [28][29][30] and epithelium-specific ETS transcription factor-1 (ESE-1) mRNA is upregulated at least 6-fold after mouse EC cells differentiate. 31) Together with the previously published findings, our expression data suggest that the ETS factors PEA3 and ESE-1 play important roles in pluripotent and tumorigenic EC cells.…”
Section: Resultsmentioning
confidence: 99%
“…ETV genes (i.e., members of the PEA3 subfamily of ETS genes) have previously been implicated as transcriptional regulators of cancer invasion and metastasis in various cancer types, and several of their targets include genes associated with metastatic dissemination (51,52,62,63). Furthermore, it has previously been proposed that ETV4 may be particularly relevant for prostate cancer progression, because it is robustly up-regulated in PC3 human prostate cancer cells, and its depletion in these cells impairs their anchorageindependent growth in cell culture (50). Interestingly, our analysis of ETV4 target gene activation in human prostate cancer has revealed that ETV4 is preferentially correlated with PI3-kinase and Ras signaling in bone metastases compared with lymph node metastases (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 A and B; SI Appendix and Datasets S4 and S5). Notably, these ETS transcription factors have been previously implicated in mediating Ras signaling in prostate (49,50) and other cancers (51,52), as well as in regulation of EMT markers, including Snail (53,54).…”
Section: Activation Of Etv4 By Pi3-kinase and Ras Signaling In Metastmentioning
confidence: 99%
“…Androgensignaling brings these two genes into proximity, thus inducing their fusion (313). Altogether, the untranslated 5'UTR region of gene TMPRSS2 (21q22) may fuse with ERG (21q22), ETV1 (7p21), SLC45A3 9 (solute carrier gene) and with HERVK, the human endogenous retrovirus gene, that in extravillous cytotrophoblasts exerts immunosuppressive properties in the defense of the fetus (314,315) (318).…”
Section: Ebvmentioning
confidence: 99%